THE IMPACT OF EMPLOYEE EMPOWERMENT AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE THROUGH WORK ENGAGEMENT AS A MEDIATING VARIABLE AT PT PABRIK KERTAS TJIWI KIMIA, TBK - Achmad Nuril Huda; Budi Eko Soetjipto; Ely Siswanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to examine the impact of employee empowerment and organizational culture on employee performance through the mediating role of work engagement at PT Pabrik Kertas Tjiwi Kimia Tbk, a pulp and paper manufacturing company. This study uses an explanatory quantitative research approach. Primary data were collected using questionnaires from 257 permanent employees in the Stationery Division, selected through probability sampling techniques. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that employee empowerment does not have a significant direct effect on employee performance. On the other hand, organizational culture is proven to have a positive and significant direct effect on employee performance. Other findings show that both employee empowerment and organizational culture significantly enhance work engagement. Work engagement itself is proven to have the strongest direct effect on improving employee performance. Furthermore, the mediation analysis results confirm that work engagement significantly mediates the relationship between employee empowerment and employee performance, as well as the relationship between organizational culture and employee performance. Practically, these findings provide managerial insights for manufacturing companies to strengthen employee performance in supporting corporate sustainability through a supportive culture and high levels of work engagement.